Monitoring COVID-19 Impacts on Households in Zambia, Report No. 1 : Results from a High-Frequency Phone Survey of Households - Finn, Arden; Zadel, Andrew (World Bank, Washington, DC, 2020)
The COVID-19 pandemic and its economic and social effects on households have created an urgent need for timely data to help monitor and mitigate the social and economic impacts of the crisis and protect the welfare of the least well-off in Zambian society. To monitor how the COVID-19 pandemic is affecting Zambia’s economy and people and to inform interventions and policy responses, the World Bank designed and conducted a rapid phone-based Household Monitoring Survey (HMS). This brief summarizes the results of the first round of the HMS, implemented between June 5 and June 26, 2020. The brief is based on a sample of 1,602 households in both urban and rural areas in all ten provinces of Zambia. The survey is representative at three levels: Lusaka, urban excluding Lusaka, and rural. The 25-minute questionnaire covers such topics as knowledge of COVID and mitigation measures, access to educational activities during school closures, employment dynamics, household income and livelihood, income loss and coping strategies, and assistance received.